Does the mobility of foreign offenders fit the general pattern of mobility? - Bruinsma, Gerben (European journal of criminology, 2012)
Research on offender mobility is directed to three main elements: distance, anchor points, and direction. Previous research in geographical criminology has revealed that: (1) the journey to crime is limited in distance and follows a distance decay pattern; (2) the home of the offender plays a central role as the starting point of crime trips; and (3) the direction of the trip is influenced by the opportunities to commit crimes. The findings are more or less accepted as 'laws' in the field. However, research on offender mobility is often limited by its method, data and sample of arrested offenders. This study, in contrast, investigated a sample of arrested foreign offenders (East Europeans) who were staying temporarily in Belgium. They lack the space awareness and routine activities of residential offenders. Using multiple methods and data, including police statistics, case file analysis and offender interviews, we investigated the travelling patterns of these offenders both quantitatively and qualitatively. The findings demonstrate that: (1) the degree of distance decay is much more moderate than generally found in the literature; (2) the official living address plays hardly any role at all as an anchor point; and (3) these offenders travel away from opportunity structures, which is different from the routine activity patterns of Belgian offenders. Overall, our findings indicate that offender mobility does not fit the accepted general pattern or 'laws' as assumed in previous research